Avaliação da Política de Assistência Estudantil (PAE) do Instituto Federal de Educação, Ciência e Tecnologia do Ceará (IFCE): a inclusão social enquanto direito dos estudantes do Campus Cedro - Bezerra, Carlos Winston Guedes (2020)
This dissertation aims to evaluate the implementation of the Student Assistance Policy (PAE) of IFCE at Campus Cedro in 2019. The formulation and implementation of the PAE result from the approval of the National Student Assistance Program (PNAES) in 2010 that aims at inclusion education for the students of Professional and Technological Education (EPT) from Federal Institutes (IF). Considering the inclusive assumption of PAE that aims to reduce social inequalities present in Brazilian education, the research seeks to: investigate the socio-historical, economic and political context that made it possible with its clashes and impasses; verify their conceptual bases and their coherence with their objectives and their local reality; apprehend the meanings and meanings of the same for the various actors involved and how their own conceptions can interfere in the implementation of the PAE. It is a case study (YIN, 2001) of a qualitative character from the perspective of in-depth assessment (RODRIGUES, 2008, 2011, 2016) and which seeks to build qualitative indicators (MINAYO, 2009) for policy evaluation. In its methodological path, it focused the evaluation on the analysis of the recent context of formulation and implementation of the PNAES in the post-constitution country from 1988 until the first year of the Bolsonaro government; in the temporal trajectory of implementing the PNAES in the IFCE and in formulating and implementing the PAE and in analyzing its content in relation to the PNAES, focusing on its guiding paradigms and the repercussions of this on the IFCE; finally, in the temporal-territorial spectrum of effective PAE at Campus Cedro in 2019. Based on bibliographic, documentary and field data (on-site observations and semi-structured interviews), the delimitation of five qualitative indicators was made: the limited range of the EA; the academic and biopsychosocial development of students; access to culture, sport, leisure and work as part of human training; combating all forms of prejudice and discrimination, still a handicap; active participation in the construction of the PAE and its publication. It concludes with the evaluation undertaken that the PAE at the Cedro Campus is still far from meeting the educational and / or biopsychosocial needs of the students in an equitable way, social inclusion through education is still a utopia for many, but it is undoubtedly what moves in the realization of the right to dream about another possible educational and societal universe.